Serologic responses correlate with current but not future bacterial shedding in badgers naturally infected with Mycobacterium bovis. Issue 4 (17th June 2021) - Jolma, Elli R.; Delahay, Richard J.; Smith, Freya; Drewe, Julian A.
Abstract: Bovine tuberculosis is a challenging cattle disease with substantial economic costs in affected countries. Eradication in parts of the United Kingdom and Ireland is hindered by transmission of the causative agent Mycobacterium bovis between cattle and European badgers ( Meles meles ). Diagnostic tests in badgers are of limited accuracy but may help us understand and predict disease progression. This study aimed to determine the practical ability of a commercially available serologic test, the Dual Path Platform VetTB assay (DPP), to predict mycobacterial shedding (i.e. infectiousness) and disease progression in badgers, and whether test outcomes were associated with re‐capture. Clinical samples collected from 2014 to 2019 from a wild, naturally infected population of badgers in southwest England were tested using mycobacterial culture (from sputum, urine, faeces, abscesses and bite wounds), an interferon‐gamma release assay and the DPP assay. Data were analysed at both individual badger and social group levels using generalised linear and cumulative‐link mixed models, and linear regression. Only the highest DPP readings [optical density relative light unit (RLU) levels] were associated with mycobacterial shedding [odds ratio (OR) for DPP levels > 100 RLU in individual badgers: 79.6, 95%CI: 14.7–848; and for social groups: OR: 7.28, 95%CI: 2.94–21.44; compared with levels < 100 RLU]. For individual badgers, RLU levels at first capture were not associated with disease progression at subsequent captures. Finally, badgers with very high DPP levels (> 1000 RLU) were four times less likely to be recaptured (OR: 0.24, 95%CI: 0.07–0.83) than those without a detectable DPP response, which might indicate enhanced mortality. We conclude that DPP levels of > 100 RLU identify badgers that are likely to be shedding M. bovis . Levels of > 1000 RLU identify badgers that are much less likely to be re‐captured. These results provide insights into the potential value of existing tests in intervention strategies for managing M. bovis in badgers.